VERIFIKASI METODE PENENTUAN SULFUR DIOKSIDA (SO2) PADA SAMPEL UDARA AMBIEN DENGAN METODE PARAROSANILIN MENGGUNAKAN SPEKTROFOTOMETER UV-VISIBELE - Anwar, Adliah; Pasaribu, Subur P.; Panggabean, Aman Sentosa (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
The research about verification method on determination of sulfur dioxide (SO2) on ambient air samples with the pararosaniline method using UV-Vis Spectrophotometer has been done. To obtain a valid measuring result, some important parameters of measurement on sulfur dioxide (SO2) in ambient air samples based on SNI 7119-7:2017. The results showed that the linearity of the measurement was very good as indicated by the correlation coefficient value was 0.9998. The limit of detection and limit of quantization was 2.7766 g/Nm3 and 7.4111 g/Nm3 respectively. The value of precision was good shown by %RSD < 2/3 CV Horwitz, and the accuracy of this method was good shown by a recovery percentage of 101.12%. Based on the results of this research, the pararosanilin method can be used to analyze sulfur dioxide (SO2) in ambient air samples with good results.